2012
DOI: 10.1002/ijfe.1466
|View full text |Cite
|
Sign up to set email alerts
|

Financial System Sophistication and Unemployment in Industrial Countries

Abstract: By using data on 21 industrial countries from 1984 to 2006 and a large number of controls, this paper studies the unemployment effects of one major characteristic of the financial system: its level of sophistication, that is, the variety of financial institutions and instruments available to the economy. The paper finds that a higher level of sophistication is likely to reduce unemployment among the total labour force as well as among high‐skilled workers. The magnitude of both effects appears to be modest. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 84 publications
(87 reference statements)
4
9
0
1
Order By: Relevance
“…The empirical studies on the relationship between innovation and unemployment are so limited in the context of macroeconomics. There are three studies as Feldmann (2013aFeldmann ( , 2013b, Matuzeviciute, Butkus, and Karaliute (2017) and Tancioni and Simonetti (2002) which are close to this study's perspective in the literature. According to microeconomic perspective, researchers focused on the effect of innovative businesses on unemployment for limited industries.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The empirical studies on the relationship between innovation and unemployment are so limited in the context of macroeconomics. There are three studies as Feldmann (2013aFeldmann ( , 2013b, Matuzeviciute, Butkus, and Karaliute (2017) and Tancioni and Simonetti (2002) which are close to this study's perspective in the literature. According to microeconomic perspective, researchers focused on the effect of innovative businesses on unemployment for limited industries.…”
Section: Introductionsupporting
confidence: 62%
“…When the studies investigating the relationship between innovation and unemployment are reviewed, it is evident that micro (firm) studies focus only on the employment effect in innovation firms. These studies do not address the impacts of competing firms in the same sector or the effects on other industries (Feldmann, 2013a(Feldmann, , 2013b. For example, in his firm-level study, Van Reenen (1997) says that innovation has a positive and significant effect on employment, while Hall, Lotti, and Mairesse (2008) found that process innovation has no significant effect on employment.…”
Section: The Relationship Between Innovation and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced financial resources as well as cultural values and norms contribute to the disadvantage observed in long-term saving and retirement income of ethnic minorities compared with the white majority (e.g. Patrinos 1997;Bauer and Zimmermann 1997;Crossan et al 2011;Mitchell, 2011a, 2011b;Lusardi et al 2012;Seto and Bogan 2013;Feldmann 2013;Kandil 2015). Previous literature shows persistent trends of disadvantage in the labour market for minority ethnic groups, which is often perpetuated in retirement (Johnson 2004;Lewis and Lloyd-Sherlock, 2009;Börsch-Supan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although over the past decades, many aspects of the lives of ethnic minorities in the UK have improved owing to greater integration and multiculturalism, there is extensive recent evidence that some disadvantage still exists, as poorer job opportunities, interrupted job histories, greater levels of self-employment and unemployment are more frequent amongst ethnic groups (Malveaux, 1999;Clark and Drinkwater, 2000;Blackaby et al, 2002;Cabinet Office, 2003;Pensions Policy Institute, 2003;Hoque andNoon, 2004, Vlachantoni et al, 2017). Reduced financial resources and cultural values and norms contribute to the disadvantage observed in long-term saving and retirement income of ethnic minorities compared with the white majority (Patrinos, 1997;Bauer and Zimmermann, 1997;Crossan et al, 2011;Mitchell, 2011a, 2011b;Lusardi et al, 2012;Seto and Bogan, 2013;Feldmann, 2013;Kandil, 2015). Previous literature shows persistent trends of disadvantage in the labour market for minority ethnic groups, which is often perpetuated in retirement (Johnson, 2004;Lewis and Lloyd-Sherlock, 2009;Börsch-Supan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%